Individual Investors in the Nepalese Securities Market: What They Know and What They Like - Dahal, Rewan Kumar (Nepal Journal of Multidisciplinary Research, 2022)
Investments in financial assets is getting much more popular nowadays. The investment made by individual investors is always guided by their own comprehension and preference over the investment. Therefore, the study aimed to examine the understating and the preference of the individual investors of the Nepalese securities market. A convenient sampling strategy was employed to obtain the essential information via structured questionnaire survey from investors at different stock brokers' sites in Kathmandu valley and collected 203 responses. Nepalese investors favoured equities and the banking sector. Even though profit was their major investing goal, they did not do a risk-return analysis. They were unhappy with investment decisions, rules, and regulations. As a result, their investing decisions were significantly influenced by their presumption of market information and understanding. This study has aided to a better comprehension of what factors contribute to shaping the individual investors' investment decisions.